What Factors Affect the Oslo Stock Exchange? - Randi Næs; Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2009)
This paper analyzes return patterns and determinants at the Oslo Stock Exchange (OSE) in the period 1980-2006. We find that a three-factor model containing the market, a size factor and a liquidity factor provides a reasonable fit for the cross-section of Norwegian stock returns. As expected, oil prices significantly affect cash flows of most industry sectors at the OSE. Oil is, however, not a priced risk factor in the Norwegian stock market. As the case in many other countries, we find that macroeconomic variables affect stock prices, but since we find only weak evidence of these variables being priced in the market, the most reasonable channel for these effects is through company cash flows.
hdl:11250/2497617
Keywords: G12; E44; 330; stock market valuation; asset pricing; factor models; generalized method of moments